PHOTOMETRIC AND SPECTROPHOTOMETRIC OBSERVATIONS OF THE CLASSICAL SYMBIOTIC STAR YY Her - A. A. Tatarnikova; E. A. Kolotilov; U. Munari; B. F. Yudin (Odessa Astronomical Publications, 2017)
The spectrophotometric and photometric observations of the classical symbiotic star YY Her both during its quiescent state and during a strong outburst in 1993 are presented.